THE EFFECTIVENESS OF THE PICTURE STORY METHOD IN INCREASING STUDENT'S READING INTEREST CLASS 2 AT SOURCE STATE ELEMENTARY SCHOOL, BANDUNG: indonesia - Okta Nur Fadila; Dwi Rohmadi Mustofa; Nurhadi Kusuma; Amrulloh Khoirul Ma'arif (Al-Ibda: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Abstract Student’s reading interest Elementary school, especially grade 2 SD Sumber Bandung, is still low because they prefer to play online games, watch television, etc. This factor causes their reading ability is still lacking. In addition, there are reading books in school institutions that are still monotonous without pictures so that children get bored easily and are not interested in reading them. This study purposed to see how effectiveness of pictural story book in increasing reading inters of grade 2 students at SD Sumber Bandung. The method has been use in this research is an experimental research method with one group pre test – post test design. The use of learning media to foster children's interest in reading is by using picture story books. This picture book is more developed if the teacher dares to be creative. This picture story book is effectively used in the second grade students of SD Sumber Bandung because it includes games and education. In the picture story book there are several learning activities including observing, telling, reading and sorting the pictures so that they become a complete story. Furthermore, the teacher can add / collaborate on strategies or methods that can support the use of other picture story books to be more innovative in each lesson. The result of this research is that picture story books are very effective in increasing reading interest of student Grade 2 SD sumber bandung Keywords :; Story book; interest in reading, SD Sumber Bandung